A source authentication and data confidentiality scheme for multicast networks - Benmachiche, Abderrahim; Ali, Salami; Messikh Azeddine, Azeddine (IIUM Press, 2016)
Source authentication and data confidentiality are needed in many multicast applications. Most research attempted to solve either the source authentication or the confidentiality of data. This paper proposes a scheme that can treat the two problems together. Our scheme uses the TESLA protocol to ensure the source authentication and XOR encryption to ensure the confidentiality of the transmitted information so that the scheme can be applied to low bandwidth applications without requiring high computation devices. Furthermore, it tolerates packet-loss. These advantages render the proposed scheme secure in terms of authentication and confidentiality and it does not cost much.